Effectiveness of subarachnoid anesthesia with morphine as a treatment for postoperative pain in cesarean section - Yuliel Varona Rodríguez; Liliam María Castillo Manresa; Adonis Cintra Dornes; Jose Carlos Acosta Abad; Aimé Batista Blanco; Ariane Sainz Cortada (Medisur)
Foundation: Postoperative pain is considered time-limited pain, often poorly controlled. Its management represents a great challenge, since postoperative analgesia must provide the mother with adequate control, and at the same time facilitate care for the baby. Objective: to evaluate the effectiveness of subarachnoid anesthesia with morphine as a treatment for postoperative pain in cesarean section. Methods: descriptive and cross-sectional study carried out at the Martín Chang Puga General Teaching Hospital, in the Nuevitas municipality, Camagüey province, between January 2021 and December 2022. 36 patients to whom subarachnoid anesthesia was applied with Hyperbaric lidocaine plus morphine for cesarean section were considered as the sample. Results: the age between 27-31 years predominated. 63.9% of cesarean patients did not report postoperative pain. Almost half of the population (47.2%) studied presented side effects with the use of intrathecal morphine, mainly pruritus. 80.5% expressed satisfaction with postoperative analgesia. Conclusions: the majority of patients were satisfied with the analgesic treatment, despite the presence of adverse effects, so that the use of intrathecal morphine is effective in the management of post-cesarean section pain.